Research Letter: PTSD has shared polygenic contributions with bipolar disorder and schizophrenia in women - Sumner, J. A.; Duncan, L.; Ratanatharathorn, A.; Roberts, A. L.; Koenen, K. C. (Psychological medicine, 2016)
Twin studies have demonstrated overlap between genetic contributions to post-traumatic stress disorder (PTSD) and other psychiatric disorders (Kremen et al. 2012). These findings have prompted interest in examining shared genetic risk between PTSD and other psychopathology at the molecular level. With genome-wide association studies (GWAS) and collaborative consortia-based efforts, replicable risk variants have been identified for schizophrenia and bipolar disorder (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014). Analyses of genetic loci in aggregate (polygenic effects; Purcell et al. 2009) have demonstrated shared genetic risk between schizophrenia, bipolar disorder, and major depressive disorder (MDD), with greatest overlap for schizophrenia and bipolar disorder (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013). Using 3742 candidate single nucleotide polymorphisms (SNPs), an initial polygenic analysis of PTSD by our group (Solovieff et al. 2014) suggested overlap in genetic risk for bipolar disorder and PTSD in European American (EA) women that was replicated in a male EA sample with genome-wide data (Nievergelt et al. 2015).